Functionalization of Alginate with Extracellular Matrix Peptides Enhances Viability and Function of Encapsulated Porcine Islets. Issue 9 (7th April 2020) - Medina, Juan D.; Alexander, Michael; Hunckler, Michael D.; Fernández‐Yagüe, Marc A.; Coronel, María M.; Smink, Alexandra M.; Lakey, Jonathan R.; de Vos, Paul; García, Andrés J.
Abstract: Translation of transplanted alginate‐encapsulated pancreatic islets to treat type 1 diabetes has been hindered by inconsistent long‐term efficacy. This loss of graft function can be partially attributed to islet dysfunction associated with the destruction of extracellular matrix (ECM) interactions during the islet isolation process as well as immunosuppression‐associated side effects. This study aims at recapitulating islet‐ECM interactions by the direct functionalization of alginate with the ECM‐derived peptides RGD, LRE, YIGSR, PDGEA, and PDSGR. Peptide functionalization is controlled in a concentration‐dependent manner and its presentation is found to be homogeneous across the microcapsule environment. Preweaned porcine islets are encapsulated in peptide‐functionalized alginate microcapsules, and those encapsulated in RGD‐functionalized alginate displays enhanced viability and glucose‐stimulated insulin release. Effects are RGD‐specific and not observed with its scrambled control RDG nor with LRE, YIGSR, PDGEA, and PDSGR. This study supports the sustained presentation of ECM‐derived peptides in helping to maintain health of encapsulated pancreatic islets and may aid in prolonging longevity of encapsulated islet grafts. Abstract : Adhesion peptide‐modified alginate microcapsules enhance functional viability of encapsulated pancreatic islets. Interactions between islets and extracellular matrix (ECM) have regulative effects on pancreatic islet survival and function. These interactions are lost during the islet isolation process necessary for islet transplantation. This study shows that incorporation of a specific adhesion peptide sequence promotes islet health and function in vitro.